Effect of elastic resistance training on the jab punch performance - Suzovic, D.; Markovic, P.; Planic, N.; Jaric, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The elastic resistance training could be an efficient method that improves the speed performance in various movement tasks (Jakubiak, Sounders, 2008). However, very few studies have explored the effects of the elastic resistance training on the rapid arm movements. The aim of the present study was to explore the efficiency of the elastic resistance training through the performance of standard jab punch. Methods: Twenty high school students (age: 18.2 ± 0.7 yr, body mass: 79.9 ± 11.4 kg, height: 1.83 ± 0.05 m; mean ± SD; all active in various sports through various school competition system) participated in the study. Experimental group (n=10) practiced jab with the applied elastic resistance over 6 weeks, whilst the control group (n=10) trained without the additional resistance. Both the punching peak speed and peak acceleration of selected body points were recorded by a 3D Qualisys system, while the markers placed lateraly on the hand, elbow, shoulder and hip. All variables were individually tested by a mixed 2-way ANOVA with the main effects being group (elastic resistance vs. no resistance) and test (pre-test vs. post-test). Results: The maximum speed of hand revealed the main effect of test (p<0.01), but not of group, and no interaction. Namely, the elastic resistance group was faster at the post-test, but the group x test interaction was somewhat below the significant level (p<0.1). However, the elastic resistance group revealed a higher gain in both the speed and acceleration of the hip and knee joint (p<0.05). Discussion: Since the study was conducted on a relatively small sample of subjects, the observed effects suggest that the ellastic training could be beneficial for improvement of rapid arm movements. Mechanisms of the improvement could be based on a higher involvement of the larger muscle groups acting in the leg and trunk joints, as we observed in the post-test of the elastic resistance group. Nevertheless, more research is needed to generalize the claims regarding the efficiency of the elastic resistance training (c.f., Jakubiak, Sounders, 2008; Stone et al. 2002) on the rapid arm movements, such as the tested jab punch. Acknowledgments The study was supported in part by a grant from Serbian Research Council (#145082)